PENGENALAN ALGORITMA PEMROGRAMAN MELALUI SIMULASI ROBOT - Abadi Nugroho (Jurusan Teknik Informatika, 2015)
Programming algorithms is one discipline that became the basic of learning a programming language. Everyone who will makes the creation of applications or information systems need to know the algorithm or the flow of the system to be made in advance. During this time the usual way of learning may seem difficult and less attractive. We will try another, more interesting way to learn a programming algorithms through a robotsimulation. In this way we are sure to make learning more attractive so that will foster interest in learning.